Glosa do wyroku Europejskiego Trybunału Praw Człowieka z dnia 27 czerwca 2024 r. w sprawie Boisteau przeciwko Polsce - Rzewuska, Magdalena (PRAWO i WIĘŹ, 2026)
The subject of the publication is the analysis of the position of the European Court of Human Rights expressed in the judgment of 27 June 2024 in the case of Boisteau v. Poland. The judgment of the European Court of Human Rights was issued following consideration of an application filed by French citizen Johann Dephaer Boisteau against the Republic of Poland, concerning the applicant’s right to respect for his family life under Article 8(1) of the Convention for the Protection of Human Rights and Fundamental Freedoms. The subject matter of the case included the issue of the complainant’s contact with his child, the execution of interim measures and the duration of the court proceedings pending in the case. The author took a positive attitude to the position of the European Court of Human Rights expressed in the commented judgment, indicating additional arguments justifying the accuracy of this view, such as the fact that both the right to the protection of family life and the right to have a case examined by an independent court without undue delay are rights that are subject to constitutional protection in the Polish legal system.